Homogenization of an alternating Robin–Neumann boundary condition via time-periodic unfolding. (April 2017) - Amar, Micol; Andreucci, Daniele; Bellaveglia, Dario
Abstract: We consider the homogenization of a parabolic problem in a perforated domain with Robin–Neumann boundary conditions oscillating in time. Such oscillations must compensate the blow up of the boundary measure of the holes. We use the technique of time-periodic unfolding in order to obtain a macroscopic parabolic problem containing an extra linear term due to the absorption determined by the Robin condition.